2015
DOI: 10.5114/aoms.2014.43672
|View full text |Cite
|
Sign up to set email alerts
|

Is faecal calprotectin equally useful in all Crohn’s disease locations? A prospective, comparative study

Abstract: IntroductionThere are data suggesting that the diagnostic usefulness of faecal calprotectin (FC) may vary depending on the Crohn's disease (CD) location. The aim of the study was to compare the diagnostic usefulness of FC in CD patients with different disease locations.Material and methodsWe prospectively enrolled 120 CD patients in the study. Disease activity was assessed by using Crohn's Disease Activity Index (CDAI), biochemical markers, and endoscopic and radiographic methods. Faecal calprotectin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 28 publications
(32 reference statements)
1
35
0
2
Order By: Relevance
“…Indeed, in this study, FC was actually used in a higher proportion of CD than UC patients, and of those, approximately one third had isolated small bowel CD. As per these supportive data, we agree with others that this is rational and appropriate given the constraints of alternative small bowel investigations …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, in this study, FC was actually used in a higher proportion of CD than UC patients, and of those, approximately one third had isolated small bowel CD. As per these supportive data, we agree with others that this is rational and appropriate given the constraints of alternative small bowel investigations …”
Section: Discussionsupporting
confidence: 85%
“…As per these supportive data, we agree with others that this is rational and appropriate given the constraints of alternative small bowel investigations. 15,26 Although this is the largest study to our knowledge to evaluate FC compared to colonoscopy disease activity assessment in relation to clinical decision-making and cost analysis in a real-world IBD cohort, there are several limitations with this type of retrospective methodology. This also includes inherent differences between the FC and colonoscopy only cohorts, especially as the latter is from an earlier time periodthis is reflected in a more aggressive treatment profile seen in the FC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has found that FC does not reliably distinguish IBD from malignancy [33], which may-indirectly-suggest that FC is not as good at distinguishing generalized inflammation from foci of inflammation. Furthermore, some studies show FC is a more reliable indicator of colonic than SB inflammation, i.e., usefulness of FC varies with location of inflammation within the gut, and there is difficulty in establishing correlation due to the heterogeneity of presentations in CD [34,35]. Figure 1 shows how LS is generally low in patients with normal SBCE; however these patients have a wide range of FC.…”
Section: Discussionmentioning
confidence: 91%
“…A colonic SES-CD = 0 was defined as "colonic inactive", and a colonic SES-CD ³1 was defined as "colonic active". (25) Statistical analyses. Descriptive statistics were presented as the mean ± SD for normal distributions.…”
Section: Methodsmentioning
confidence: 99%
“…(9,18) However, the validity of this approach is not known, and the appropriate biomarkers of SB lesion activity in established CD have not been determined to date. (19)(20)(21)(22)(23)(24)(25) We consider that established ileocolonic CD may be detected by ICS and, if the colonic endoscopic findings correlate with small bowel endoscopic findings, small intestinal endoscopic findings may be predicted. However, there is no previous study that reported a correlation between the endoscopic findings of the small bowel and colon in patients with established ileocolonic CD.…”
mentioning
confidence: 99%